Pelatihan Pembuatan Brosur Promosi Melalui Aplikasi Canva pada Produk Jamu Sedayu Argomulyo - Adji Syahputra (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Business development in the current era is becoming more intense, with many opportunities to start a business, many other businesses are experiencing a decline in turnover because they are unable to compete with competitors who have similar products. The solution to this problem can be overcome by creating promotions. The most affordable and long-lasting promotional media is brochures. Omah Jamu is a business in the field of herbal drinks, with good promotion, this business can gain more reputation which is useful for inviting other potential consumers. This service involves creating a brochure with the Omah Jamu business profile with the results being a ready-made brochure for the Omah Jamu business